Broomstick lace crochet : a new look at a vintage stitch, with 20 stylish designs - Wolfe, Donna ([S.l.] : Stackpole Books, 2015)
Discover all 20 finished designs in our exclusive Look Book! Learn an updated take on the vintage art of broomstick lace with easy-to-follow photo tutorials! Made using a super-huge needle (the "broomstick") and a crochet hook, this technique creates a very distinctive cluster lace stitch that's fun and fast to crochet. Photo tutorial teaches you the basic stitch using single crochet; additional broomstick lace tutorials include how to increase and decrease, work in the round, change color, and work broomstick lace with different stitches 250 step-by-step color photos walk you through the entire process as you learn this exciting new technique Includes 20 original designs for broomstick lace, ranging from accessories to baby items to designs for the home.